Karakterisasi Morfologi dan Sifat Kuantitatif Gandum (Triticum aestivum L.) di Dataran Menengah - Widowati, Sartika; Khumaida, Nurul; Ardie, Sintho Wahyuning; Trikoesoemaningtyas, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTIndonesia is one of the largest wheat importers. Suitable environmental condition for wheat needs to be studied if wheat is going to be widely cultivated in Indonesia. The adaptability of wheat grown in various climates and altitudes is one of the important aspects. The objective of this experiment was to study the quantitative and morphological character of wheat grown in middle land (540 m asl) in Bogor, West Java. The experiment was arranged in randomized complete block design with three replications. Wheat genotypes used were three national varieties (Nias, Selayar, and Dewata), four new improved varieties (Guri 3 Agritan, Guri 4 Agritan, Guri 5 Agritan, and Guri 6 Unand), and one introduced genotype (SBD). Data were collected for several quantitative variables and seventeen morphological characters based on UPOV descriptor. The result showed that wheat growth was restricted in Bogor. Genotype determined plant height, leaf number, ear length, root length, number of spikelet, harvest time, seed weight, number of tillers, and plant biomass. Based on ear length, grain weight, and plant biomass, Guri 3 Agritan had the highest production than the other genotypes.Keywords: diversity, genetic relationship, high temperature, introduced genotype, phylogenetic